Synthesis of Some N-Amino Quinolin-2-ones form 4-Methyl Coumarins - Gharde, A.D. (Asian Journal of Chemistry, 2010)
4-Mcthyl coumarins readily react with bydrazinc hydrate in alkaline medium to give N-amino-quinolin-2-ones. The compounds were characterised by elemental analysis, chemical properties and IR and NMR spectra.